Parenting Style and Adolescent Mental Health Outcomes: A Cross-Sectional Study Among Senior High School Students in Bandung, Indonesia - Juliyanti Juliyanti; Vera Tiara Sany (Griya Eka Sejahtera, 2026)
Background: Adolescent mental health problems are increasing and have become a significant public health concern, as adolescence represents a critical developmental transition characterized by physical, cognitive, emotional, and social changes. Parenting style is recognized as an important determinant of adolescent mental health. Inappropriate parenting styles, such as authoritarian and permissive approaches, have been associated with emotional problems, including anxiety, depression, and behavioral regulation difficulties.Methods: This study employed a quantitative approach with a cross-sectional design. The sample consisted of 246 students recruited from five senior high schools in Bandung Indonesia. Adolescent mental health was assessed using the Strengths and Difficulties Questionnaire (SDQ), while parenting style was measured using the Parenting Style and Dimensions Questionnaire (PSDQ). Data were analyzed using Spearman’s rank correlation test.Results: The majority of respondents reported democratic parenting (66.7%), and more than half were classified as having normal mental health status (51.6%). Statistical analysis revealed a significant relationship between parenting style and adolescent mental health (p = 0.032; p < 0.05), with a very weak positive correlation (r = 0.136).Conclusion: Parenting style was significantly associated with adolescent mental health, although the strength of the relationship was very weak. Democratic parenting was associated with more favorable mental health outcomes compared to authoritarian and permissive parenting styles. These findings highlight the importance of collaborative efforts between families and schools to support optimal adolescent psychological development.